“They Were Noble Automatons Who Knew Not What They Did:” Volition in Jaynes' The Origin of Consciousness in the Breakdown of the Bicameral Mind - Moore, James W. (Frontiers in Psychology, 2021)
An important question in consciousness research concerns its origins. In Julian Jaynes’ book, The Origin of Consciousness in the Breakdown of the Bicameral Mind (Jaynes, 1977), he suggests that consciousness arose rather recently in human history, some time between the composition of The Iliad and The Odyssey. Although Jaynes’ work as a theory of consciousness has achieved a great deal of attention (and indeed criticism), what has not been widely noted is the prominent role of volition in his theory. In this article I hope to draw attention to these overlooked aspects of his theory, in particular the fact that volition is central to Jaynes’ definition of consciousness and that it is changes in the nature of volitional experience that mark, for Jaynes, the emergence of consciousness.